A Mixed-Methods Study of Risk Factors and Experiences of Health Care Workers Tested for the Novel Coronavirus in Canada. Issue 9 (14th September 2022) - Okpani, Arnold Ikedichi; Barker, Stephen; Lockhart, Karen; Grant, Jennifer; Delgado-Ron, Jorge Andrés; Zungu, Muzimkhulu; Naicker, Nisha; Ehrlich, Rodney; Yassi, Annalee
Abstract : A reappraisal of mitigation strategies against occupational hazards is required to ensure that all health workers – not just those in perceived "high-risk" work environments - are protected. This will mean reducing community-level risks and ensuring that the same level of IPC measures, PPE training and supply is available when needed. Abstract : Objective: The aims of this study were to investigate occupational and non–work-related risk factors of coronavirus disease 2019 among health care workers (HCWs) in Vancouver Coastal Health, British Columbia, Canada, and to examine how HCWs described their experiences. Methods: This was a matched case-control study using data from online and phone questionnaires with optional open-ended questions completed by HCWs who sought severe acute respiratory syndrome coronavirus 2 testing between March 2020 and March 2021. Conditional logistic regression and thematic analysis were utilized. Results: Providing direct care to coronavirus disease 2019 patients during the intermediate cohort period (adjusted odds ratio, 1.90; 95% confidence interval, 1.04 to 3.46) and community exposure to a known case in the late cohort period (adjusted odds ratio, 3.595%; confidence interval, 1.86 to 6.83) were associated with higher infection odds. Suboptimal communication, mental stress, and situations perceived as unsafe were common sources of dissatisfaction. Conclusions: Varying levels of risk between occupational groups call for wider targeting of infection prevention measures. Strategies for mitigating community exposure and supporting HCW resilience are required.